Microplastics in Invasive Freshwater Mussels (Dreissena sp.): Spatiotemporal Variation and Occurrence With Chemical Contaminants - Hoellein, Timothy; Rovegno, Catherine; Uhrin, Amy V.; Johnson, Ed; Herring, Carlie (Frontiers in Marine Science, 2021)
Invasive zebra and quagga mussels (Dreissena spp.) in the Great Lakes of North America are biomonitors for chemical contaminants, but are also exposed to microplastics (< 5mm). Little research has examined in situ microplastic ingestion by dreissenid mussels, or the relationship between microplastics and chemical contaminants. We measured microplastics and chemical contaminants in mussel tissue from Milwaukee Harbor (Lake Michigan, USA) harvested from reference locations and sites influenced by wastewater effluent and urban river discharge. Mussels were deployed in cages in the summer of 2018, retrieved after 30 and 60 days, sorted by size class, and analyzed for microplastics and body burdens of three classes of contaminants: alkylphenols, polyaromatic hydrocarbons, and petroleum biomarkers. Microplastics in mussels were higher in the largest mussels at the wastewater-adjacent site after 30 days deployment. However, there was no distinction among sites for microplastics in smaller mussels, and no differences among sites after 60 days of deployment. Microplastics and chemical contaminants in mussels were not correlated. Microplastics have a diversity of intrinsic and extrinsic factors which influence their ingestion, retention, and egestion by mussels, and which vary relative to chemicals. While dreissenid mussels may not serve as plastic pollution biomonitors like they can for chemical contaminants, microplastics in dreissenid mussels are widespread, variable, and have unknown effects on physiology, mussel-mediated ecosystem processes, and lake food webs. These data will inform our understanding of the spatial distribution of microplastics in urban freshwaters, the role of dreissenid mussels in plastic budgets, and models for the fate of plastic pollution.